2016
DOI: 10.1016/j.jacc.2016.05.085
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients With Atrial Fibrillation Undergoing Percutaneous Coronary Intervention

Abstract: AF is common among patients undergoing PCI. AF is associated with older age, the presence of other comorbidities, and independently associated with in-hospital post-procedural heart failure, cardiogenic shock, and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 34 publications
5
50
2
2
Order By: Relevance
“…The two groups were comparable at the rates of all-cause death, nonfatal MI, and repeat unplanned revascularization ( P > 0.05 for all). As expected, patients with AF undergoing coronary stenting had significantly worse outcomes, as compared to patients without AF, which is in accordance with most recent studies,[7822] although in earlier study, AF was not independently predictive of mortality or major adverse cardiovascular events after 1 year except cerebrovascular events, bleeds, and vascular complications. [23] Our results differed from those previous studies[7814] in that no significant difference regarding the incidence of all-cause mortality at 12-month follow-up was found between AF and non-AF patients undergoing coronary stenting.…”
Section: Discussionsupporting
confidence: 90%
“…The two groups were comparable at the rates of all-cause death, nonfatal MI, and repeat unplanned revascularization ( P > 0.05 for all). As expected, patients with AF undergoing coronary stenting had significantly worse outcomes, as compared to patients without AF, which is in accordance with most recent studies,[7822] although in earlier study, AF was not independently predictive of mortality or major adverse cardiovascular events after 1 year except cerebrovascular events, bleeds, and vascular complications. [23] Our results differed from those previous studies[7814] in that no significant difference regarding the incidence of all-cause mortality at 12-month follow-up was found between AF and non-AF patients undergoing coronary stenting.…”
Section: Discussionsupporting
confidence: 90%
“…Patients commonly have more than one thrombotic condition. Approximately 10–15% of individuals who require PCI have a history of AF . Consequently, these individuals may be prescribed a TT regimen.…”
Section: Patients With Multiple Indicationsmentioning
confidence: 99%
“…Consequently, these individuals may be prescribed a TT regimen. Major bleeding is already concerning in the setting of DAPT; however, when an anticoagulant is added, the risk for bleeding further increases . Clinicians are more experienced in using clopidogrel and warfarin as a part of TT, compared with other P2Y12 inhibitors or the DOACs.…”
Section: Patients With Multiple Indicationsmentioning
confidence: 99%
“…Atrial fibrillation (AF) has been reported in 3% to 12% of patients undergoing percutaneous coronary intervention (PCI) . The combination of vitamin K antagonists (VKA) with aspirin and clopidogrel—called “triple therapy”—was associated with an increased risk of major bleeding up to 2.2% within the first month and 12% at 1 year in acute coronary syndromes (ACS) patients …”
Section: Introductionmentioning
confidence: 99%